Detail reproduction of elastomeric materials: effect of viscosity and groove geometry / Nik Zarina Nik Mahmood ... [et al.] - Nik Mahmood, Nik Zarina (Faculty of Dentistry, 2015)
Objective: To evaluate the effect of type of viscosity and groove on surface detail reproduction of elastomeric impression materials. Methods: Two polyvinylsiloxane and polyether elastomeric impression materials were investigated. An aluminium cylindrical reference block with V- and U-shaped grooves of 1 mm and 2 mm in depth was machined using CAD-CAM system. Impressions of the block were taken to produce 35 master dies. Each die was immersed in distilled water for 5 minutes prior to impression making. Surface topography of the dies and impressions were captured using Alicona Imaging System. Mean difference in depth between the master dies and corresponding impressions' grooves were analyzed. Results: Type of viscosities and groove showed significant main effects on surface detail (p < .01), but no significant interaction was observed between the two (p > .01). Express™ putty/light exhibited the lowest mean difference in depth for all grooves. The highest mean difference for U₁ (38.3|jm ± 21.55), U₂ (52.96pm ± 30.39)^ (45.02pm ± 34.82) and V₂ (58.44pm ± 44.19) was obtained from Impregum medium, Aquasil medium, Impregum™ heavy/light and Impregum™ heavy/light groups respectively. Conclusion: Express putty/light-bodied material produced the best surface detail, and Ushaped groove showed superior detail reproduction.